MICROTEACHING AS A PLATFORM FOR PROMOTING EFL PRESERVICE TEACHER AS A REFLECTIVE PRACTITIONER - Khofifatudzikriyah Khofifatudzikriyah; Nabilah Nabilah; Turini Erawati; Ratna Prasasti Suminar (Universitas Duta Bangsa Surakarta, 2026)
The study aimed to investigate the impact of self-reflection on developing professional identity?and teaching confidence among EFL pre-service teachers in micro-teaching practices. 18 EFL pre-service teachers participated in the study, who had undergone a micro-teaching course employing self-reflection forms designed to prompt analysis of their teaching experiences. Using thematic analysis, three key themes emerged: (1) establishing rapport with students, (2) sense of teaching competence, and (3) developing an identity as a reflective practitioner. The findings demonstrate that reflective practice helps pre-services teachers connect theory with practice, improve instructional decision-making, and fostering an environment in which pre-service teachers feel comfortable reflecting on their teaching and trying out new approaches enables them to become more flexible, reflexive, and self-aware teachers in their eventual classrooms.